math need asap

posted by .

5/8 x+1/16 x=11/16+x
16*(5/8 x+1/16 x) = 16(11/16+x)
80 + x + 16 + x= 11 + 16x
80 + 2x + 16 = 11 + 16x
-x = 18x (divide by 1)
x = 18

Did I do this correctly?

  • math need asap -

    no, after multiplying by 16 you get
    10x + x = 11 + 16x
    etc

  • math need asap -

    10x + x = 11 + 16x, so the next step is:

    11x = 11 + 16x (get x-terms on the left.)

    -x = 11 (divide by -1.)
    x = 11

    Is this now correct?

  • math need asap -

    11x = 11 + 16x

    Subtracting 16x from both sides:

    -5x = 11

    Now divide by -5.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Algerbra

    how do you solve 7(3x+4)=8(2x+5)+13 expand the parenthesis...I will do the left side.. 21x + 29= Now, subtract sixteen x from both sides, and subtract 28 from both sides. I will be happy to check your work. 7(3x+4)=8(2x+5)+13 21x + …
  2. algebra

    Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask for help with this and forgot to add the problem. can anyone help me understand how to do this?
  3. Algebra

    There are two solutions to | 16x - 5 | = 3. The greatest solution is ___. Since the expression, 16x - 5, can be either positive or negative, solve for both. 16x - 5 = 3 16x = 8 x = .5 -(16x - 5) = 3 -16x + 5 = 3 -16x = -2 x = 1/8 You …
  4. algebra

    x^2 +16x+64 x^2+16x=64 (x=3)^2=16x-64 16x=-64 x=-4 Check this problem please
  5. math, really need some feedback asap.

    5/8 x+1/16 x=11/16+x 16*(5/8 x+1/16 x) = 16(11/16+x) 10x + x = 11 + 16x, so the next step is: 11x = 11 + 16x (get x-terms on the left.) -x = 11 (divide by -1.) x = 11 Is this correct?
  6. Math

    5(-3x - 2) - (x - 3) = -4(4x + 5) + 13 Answer Multiply factors. -15x - 10 - x + 3 = -16x - 20 +13 Group like terms. -16x - 7 = -16x - 7 Add 16x + 7 to both sides and write the equation as follows 0 = 0
  7. math

    The question is (2x+1)^2-2(2x^2-1) in simplest form Is this correct?
  8. Math

    I sent this in a little while back but the file got corrupted and I have to re do it and I forgot the answer please if it is not done today I fail the year. Simplify the polynomial 16x^2 + 2 + 2x - 15x^2 - 1 + 14x A:31x^2 + 16x + 1*** …
  9. 9th grade algebra (completing square)

    Can you check the following? A1. (2x + 3)^2 = 25 sqrt(2x + 3)^2 = +-sqrt(25) 2x + 3 = +- 5 2x + 3 = 5, 2x + 3 = -5 2x = 2, 2x = -8 x = 1, x = -4 {-4, 1} A2. x^2 + 14x + 45 = 0 x^2 + 14x + __ = -45 + __ x^2 + 14x + 49 = -45 + 49 (x
  10. Math

    1. 16x^2 + 2 + 2x - 15x^2 - 1 + 14x a. 31x^2 + 16x + 1 b. x^2 - 12x + 1 c. x^2 + 16x + 1* d. x^2 + 16x + 2 2. 3x^2 + 6 - 2x + 5x - 4^2 + 9 a. -x^2 + 3x + 15* b. 7x^2 + 3x + 3 c. x^2 - 3x + 15 d. -x^2 + 7x + 15 3. 2x^2 + 6x - 7x + 8 …

More Similar Questions